The Intersection of Religious Charter Schools and Urban Catholic Education: A Literature Review - Horning, Craig N. (Catholic Education: A Journal of Inquiry and Practice, 2013)
This paper analyzes how an emerging form of schooling—“religious” charter schools—may influence the future of urban Catholic elementary education in America. Specifically, it synthesizes the literature related to religious charter schools and Catholic education. The paper investigates if a common understanding of religious charter schools is salient in the literature. In addition, it analyzes the benefits and challenges to this type of school within the context of Catholic education. The synthesis of the literature on the interplay between religious charter schools and urban Catholic elementary schools is the first of its kind. The conclusions of this paper indicate that while the religious charter school terminology is problematic when used in discussions about the future of urban Catholic elementary schools, the concept of such schools merit further reflection and research. These amorphous schools may provide new opportunities and benefits to the Catholic community and others invested in urban education, but they are challenging to implement in practice. The most likely beneficial scenario that emerged in the literature is the leasing of former Catholic school facilities to charter schools and subsequently developing before- or after-school religious education programs when there is no alternative to closing a parochial school. In addition, developing positive relationships with charter schools may result in additional income for struggling urban parishes as well as opening new doors for religious education programming and outreach to the urban poor. Challenges to religious charter schools within the context of Catholic education include church and state complications related to public funding, religious identity issues, legal concerns, increased competition for Catholic schools, and the fact that they are not Catholic schools. Lastly, there is no clear legal consensus on the viability of public charter schools that accommodate religion. This invites the need for scholarly research, advocacy, and public policy work by those interested in the future of urban education in America.